Management training in organisations : texts, cases, and simulated exercises - Dayal, Ishwar (New Delhi : Prentice-Hall of India, 1970)
This book is written for management and trainers. The book reviews the significant issues involved in the training of managers and considers how training should be integrated with the total activities of the enterprise.
"Eastern economy edition."
Includes bibliographical references p.161-163
hza 13/07/2018
Loans
Keywords: Industrial management; Indian